Ternary GdYO high k oxide films for next-generation gate dielectrics and their annealing temperature effects. Issue 8 (1st June 2019) - Li, Shuan; Wu, Yanqing; Fu, Kai; Guo, Yanru; Zheng, Jie; Tian, Wenhuai; Li, Xingguo
Abstract: As the feature size of integrated circuits continues to shrink, the key challenge is to find suitable gate dielectric materials to replace SiO2 and HfO2 to reduce leakage current density. In this work, ternary GdYO (GYO) high k films are prepared by radio frequency (RF) sputtering method and are compared with binary Gd2 O3 and Y2 O3 for their performance as gate dielectrics. The behaviors of these three samples are comprehensively investigated by x-ray diffraction, atomic force microscopy, UV-Visible spectroscopy, electrical measurements and X-ray photoelectron spectroscopy. Result shows that GYO films exhibits excellent performance as gate dielectrics for metal-oxide-semiconductor (MOS) capacitors, showing high dielectric constant (high k ) of 20.94 and low leakage current density of 1.5 × 10 −2 A/cm 2 . In addition, we show the effects of various annealing temperature from 400 to 700 °C on microstructure, band gap and electrical properties of GYO thin films. The results suggest GYO thin films annealing at 500, 600 and 700 °C can act as next-generation gate dielectrics, featuring for large band gaps of 5.31, 5.37 and 5.55 eV, high k values of 20.94, 18.69 and 17.67 as well as low leakage current density of 1.5 × 10 −2, 1.54 × 10 −3 and 9.98 × 10 −4 A/cm 2 . Finally, the leakage current density transport mechanisms of all samples have been discussed in detail.